A polytree-based adaptive polygonal finite element method for topology optimization of fluid-submerged breakwater interaction. (1st September 2018) - Vu-Huu, T.; Phung-Van, P.; Nguyen-Xuan, H.; Abdel Wahab, M.
Abstract: The polytree-based adaptive polygonal finite element method was recently proved to be very efficient for a wide class of mechanics problems. In this study, we further exploit its advantages for topology optimization of fluid-submerged breakwater interaction. Due to the inherent limitations of triangular and quadrilateral elements for topology optimization, an alternative formulation of using arbitrary polygons based on the Wachspress coordinate is employed for structural domain. In addition, we use a polytree-based adaptive technique to enhance the accuracy for topology problem in structural domain with a minimum number of degrees of freedom (DOF). We apply this method to fluid–structure interaction (FSI) problems and then finding an optimal shape of submerged breakwater (SBW), which is as a special kind of coastal structure located in front of the beach and underwater to protect the landside from the erosion. Several numerical results demonstrate the effectiveness of the present method. It is observed that the obtained results are in good agreement with reference solutions.